Increase of the productivity of wireless networks on government threshold base fragmen-tations of packages of data - Толстикова, Е. П.; Хемраев, А. К. (Problems of Informatization and Management, 2010)
The analysis of factors, influencing on the performance of wireless networks of standard of 802.11g is conducted, the mechanism of fragmentation is Considered and the results of research of influencing of threshold of fragmentation on the carrying capacity of wireless network are presented